Observation on One Lane Rigid Pavement at Jasin Plus Expressway For an Alternative Road With High Volume Traffic Area - Hot, Luqman Nul Hakim; Aman, Mohamad Yusri (Recent Trends in Civil Engineering and Built Environment, 2021)
Rigid pavement or concrete pavement are the kind of roads available in Malaysia. It is well known that the cost is slightly higher than the flexible pavement but it is safe, comfortable and effective for road users. These rigid pavement roads are often used on highways, high traffic volumes, accidents, heavy traffic lanes and intersections. It has raised many questions that are of interest to the researcher to do this research. This study has been conducted to answer all previous questions while investigating the performance of rigid pavement. The tests involved in observing the road performance of the rigid pavement types are the sound test, the speed test, the volume of traffic, the skid resistance test using the British Pendulum tester, and its dimension. All tests were conducted at the North-South Highway of Jasin area because the area has a rigid pavement. An interview with Consultants and contractor engaged directly in the rigid pavement construction. Based on site test, the data shown that the optimum performance of rigid pavement is pass for standard quality in heavy traffic area road.. The interview of road specialist such as consultant and contractor to verified or support of theory that rigid pavement is suitable for heavy traffic area at the same time have an alternatives for low the cost maintenance and construction. In conclusion, awareness of concrete type roads as quality and ideal roads is well known but is still less widely used in Malaysia because of high cost, especially in areas with high volume of vehicles daily.